Reverse Logistics and Supply Chains: A Structural Equation Modeling Investigation - Khalili-Damghani, Kaveh; Tavana, Madjid; Najmodin, Maryam (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
The process of transforming rawmaterials into final products and delivering those products to customers, knownas supply chain (SC) management, is becoming increasingly complex. Most of SCmanagement research has been concerned with procurement and production. However, recently,  it has becomeincreasingly important to extend SC issues beyond the point of sale to reverselogistic (RL) where the flow of returned products is processed from thecustomers back to the collection centers for repair, remanufacturing ordisposal.  We propose a conceptual frameworkand empirically investigate the relationship between the key factors in RL and SCperformance measurement using a series of hypotheses. Structural equation modeling(SEM) is used to test the hypotheses. The results reveal insightful informationabout the effects of RL factors on the SC performance.